RESPONSE OF GA3 SOAKING CONCENTRATION TO THE VIABILITY AND VIGOR OF SEEDS OF TWO VARIETIES OF PAPAYA (CARICA PAPAYA L.): RESPON KONSENTRASI PERENDAMAN GA3 TERHADAP VIABILITAS DAN VIGOR BENIH DUA VARIETAS PEPAYA (CARICA PAPAYA L.) - Wulan Julia Wati; R. Wahyono Widodo; Kovertina Rakhmi Indriana (ROCE : Jurnal Pertanian Terapan, 2024)
The purpose of this study was to determine the effect of the comparison of soaking concentrations of GA 3 on the viability and vigor of seeds of two varieties of papaya. The experiment was carried out in the laboratory and screen house of the Food Crops and Horticulture Seed Supervision and Certification Center (BPSBTPH) of the Food Crops and Horticulture Service, Jawa Barat Province, Bojongsoang, Bandung Regency, at an altitude of 630 m above sea levels from April to May 2023. The design used was an environmental design using a two-factor Split Plot Design which was repeated three times. The first factor as the main plot was the variety consisting of two stages including v1 (Callina variety) and v2 (PY ASA 01 variety). The second factor as a plot for comparison of GA3 concentrations contained 5 levels including k0 (0 mgL-1 water), k1 (50 mgL-1 water ), k2 (100 mgL-1 water), k3 (150 mgL-1 water), k4 (200 mgL-1 water). The experimental results showed an interaction between soaking concentration of GA3 and variations in germination rate, germination rate, root length, plant vitality, and plant dry weight, but no interaction occurred on germination time, plant height, stem diameter, number of leaves, root volume and the extinction ratio. Root (NPA). Testing the immersion concentration of GA3 150 mgL-1 on the Callina variety gave better growth in germination power, germination speed, root length, plant fresh weight, and plant dry weight compared to the PY ASA 01 variety. Independently the variety only had a higher root volume effect on the Callina variety offspring of the PY ASA 01 variety. Meanwhile, the soaking concentration of GA3 affected stem diameter, root volume, and NPA. GA3 immersion concentration of 150 mgL-1 water produced the highest stem diameter, root volume, and NPA. Application of the optimum soaking concentration of GA3 for the Callina variety of 141.87 mgL-1 water resulted in a maximum dry weight of 0.8274 grams, while  the optimum soaking concentration of GA3 for PY ASA 01 of 150.5 mgL-1 water resulted in a maximum dry weight of 0.610 grams.